SPORTS COACHES’ LEARNING AS A SOCIAL PARTICIPATION PROCESS: A PERSPECTIVE FOR SCIENTIFIC RESEARCH - Brasil, Vinicius Zeilmann; Ramos, Valmor; Backes, Ana Flávia; Ristow, Leonardo; Milistetd, Michel; Nascimento, Juarez Vieira do (Movimento, 2021)
This theoretical essay presents a set of concepts from the Social Theory of Learning (STL) and discusses its implications for research focused on sports coaches’ learning and development. The STL provides a broad analytical and instrumental scope with potential for understanding and promoting coaches’ learning. The main thematic focuses of the research agenda in this field reflect the STL’s conceptual framework. The contributions made by these studies meet the demand for using theoretical frameworks that preserve coaches learning’ complexity, social nature and contextual issues.